ANÁLISE DA REDE DE APOIO DE PAIS DE CRIANÇAS NASCIDAS COM MICROCEFALIA NO CONTEXTO DA EPIDEMIA DO VÍRUS ZIKA. - COSTA, Roama Paulo Ulisses Vaz da (2019)
This article aims to understand the role of support networks in the care of children with Zeca virus microcephaly. This is a qualitative study that is part of the quantitative and qualitative research project titled "Zika virus congenital syndrome, serum prevalence and spatial and temporal analysis of Zika and Chikungunya virus in Maranhão", carried out at the State Reference Center for Neurodevelopment, Assistance and Rehabilitation of Children (NINAR), in São Luís, from April 2017 to February 2018. The parents of children with microcephaly who participated in this study participated in the study. The techniques of data collection were structured and semi structured interviews with three couples, 15 mothers, totaling 18 interviews. The sample was defined by the saturation criterion. Content analysis was carried out in the thematic modality. In this study the support networks were divided into informal support network and formal support network. The formal support networks define relationships that occur in the professional scope, while the informal support networks are characterized by the relationships of greater affective and personal relevance. Informal support networks took center stage in front of the formal support network, which weakens the government's performance and puts into check the programs implemented by the same to cope with the Zika virus epidemic and its comorbidities.